2002
DOI: 10.1007/s00464-001-9152-0
|View full text |Cite
|
Sign up to set email alerts
|

The duration of hemodynamic depression during laparoscopic cholecystectomy

Abstract: Patients undergoing laparoscopic cholecystectomy experience significant hemodynamic depression with pneumoperitoneum. These changes are short-lived and lose their statistical significance at 10 min from the time a patient undergoes pneumoperitoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 15 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Recent studies recommend a moderate to low IAP (b12 mm Hg) as it limits the alteration in splanchnic perfusion, and consecutive organ dysfunctions will be minimal, transient, and will not influence the outcome [10]. Zuckerman and Heneghan [18] demonstrated that these changes are short lived and lose their statistical significance at 10 minutes from the time a patient undergoes pneumoperitoneum.…”
Section: Cardiovascular Effectsmentioning
confidence: 97%
“…Recent studies recommend a moderate to low IAP (b12 mm Hg) as it limits the alteration in splanchnic perfusion, and consecutive organ dysfunctions will be minimal, transient, and will not influence the outcome [10]. Zuckerman and Heneghan [18] demonstrated that these changes are short lived and lose their statistical significance at 10 minutes from the time a patient undergoes pneumoperitoneum.…”
Section: Cardiovascular Effectsmentioning
confidence: 97%
“…To adjust factors affecting intraoperative pressure, the BP at the beginning of CO 2 insufflation was compared with the mean BP within 30-60 min after insufflation. This is supported by the knowledge that hemodynamic changes begin to return to the pre-insufflation state via compensatory mechanisms approximately 15 min after gas insufflation (16). Nonetheless, the potential impact of each of these factors remains a limitation of this study.…”
Section: Discussionmentioning
confidence: 90%
“…6 Cardiac depression is usually transient with cardiac index returning to baseline levels within 10e15 minutes after abdominal insufflation. 8 At an IAP of 15 mmHg, there is an increase in systemic vascular resistance (SVR) and afterload due to compression of the abdominal aorta and increased catecholamine, vasopressin and renin angiotension activity. 2 Raised SVR increases mean arterial pressure.…”
Section: Cardiovascular Effects (mentioning
confidence: 99%